Governance Mechanisms, Managerial’s Commitment Bias and Firm’s Investment Decision Escalation: Failure of Firm’s Crises Communication: Bayesian Network Method - Fadhila, Hamza; Ali , Azouzi Mohamed; Anis, Jarboui (Asian Journal of Empirical Research, 2014)
This paper studies the role of governance mechanisms, CEO’s cognitive characteristics and firms’ financial features in justifying the CEO’s escalatory behavior in firm’s investment decision. This study aims to provide evidence as to whether managers consider the persuasive influence of governance mechanisms and the firm’s financial indicators to persevere his initial investment decision while he notes a high level of commitment bias. The proposed model of this paper uses Bayesian Network Method to examine this relationship. CEO’s cognitive characteristics have been measured by means of a questionnaire comprising several items. As for the selected sample, it has been composed of some 220 Tunisian executives. Our results have revealed the inefficient role of governance mechanisms as a persuasive communication. Managers who note a high commitment level per severe a failed course of action and ignore the governance pressure and the firm financial strength. This article has implications for the development of new referential in building corporate governance system by incorporating the commitment dimension.